2020
DOI: 10.1016/j.biocon.2020.108681
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the European Natura 2000 network at protecting Western Europe's agro-steppes

Abstract: Agro-steppes, a key bird habitat, are declining inside and outside Natura 2000 sites.• Agro-steppes are being converted mostly to permanent and irrigated crops.• Declines of agro-steppe area were 45% slower within Special Protected Areas.• The area lost in the studied SPAs could hold more than 500 great bustards.• Effective protection of Network sites is needed to achieve CBD conservation targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
(77 reference statements)
2
11
0
Order By: Relevance
“…S4 56 ). These changes were mostly located outside SPA, in accordance with the findings of recent studies 37 , 57 that also reported habitat loss outside these protected areas, in contrast with a greater habitat persistence within SPA. Our results are also consistent with those found in Spain, where declines in little bustard density are correlated to habitat loss, and fallow land in particular 39 .…”
Section: Discussionsupporting
confidence: 91%
“…S4 56 ). These changes were mostly located outside SPA, in accordance with the findings of recent studies 37 , 57 that also reported habitat loss outside these protected areas, in contrast with a greater habitat persistence within SPA. Our results are also consistent with those found in Spain, where declines in little bustard density are correlated to habitat loss, and fallow land in particular 39 .…”
Section: Discussionsupporting
confidence: 91%
“…An abundance model tested in Spain (Martín et al 2012b) showed that non-irrigated herbaceous vegetation cover was higher in places visited by Great Bustards than in places where the species was absent, and one of the defining component of the final abundance model was the non-irrigated area. This was confirmed by a study from Gameiro et al (2020) showing that the abundance of Great Bustards is highly dependent on the extent of the agro-steppe habitat in the Iberian Peninsula, and the recent negative change affecting these habitats was the expansion of plantations and irrigated crops. Moreover, a significant reduction or extinction of some Portuguese Great Bustard populations was largely due to irrigation (Pinto et al 2005).…”
Section: Introductionmentioning
confidence: 60%
“…This unique result (Alonso 2014) is now threatened by an incompetently controlled agro-economic development (Palacín et al 2012). Although the habitat-destroying effect of the spread of irrigated farming is clear, it is still feasible that it will remain hidden for a while at population level because the positive effects of diversified conservation activity may outweigh it (Gameiro et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations